Exploring Changes in the Microbiota of Aedes albopictus: Comparison Among Breeding Site Water, Larvae, and Adults - Scolari, Francesca; Sandionigi, Anna; Carlassara, Martina; Bruno, Antonia; Casiraghi, Maurizio; Bonizzoni, Mariangela (Frontiers in Microbiology, 2021)
The mosquito body hosts highly diverse microbes, which influence different physiological traits of both larvae and adults. The composition of adult mosquito microbiota is tightly linked to that of larvae, which are aquatic and feed on organic detritus, algae and prokaryotic microorganisms present in their breeding sites. Unravelling the ecological features of larval habitats that shape the structure of bacterial communities and their interactions with the mosquito host is still a poorly investigated topic in the Asian tiger mosquito Aedes albopictus, a highly invasive species that is vector of numerous arboviruses, including Dengue, Chikungunya and Zika viruses. In this study, we investigated the composition of the bacterial community present in the water from a natural larval breeding site in which we separately reared wild-collected larvae and hatched eggs of the Foshan reference laboratory strain. Using sequence analysis of bacterial 16S rRNA gene amplicons, we comparatively analyzed the microbiota of the larvae and that of adult mosquitoes, deriving information about the relative impact of the breeding site water on shaping mosquito microbiota. We observed a higher bacterial diversity in breeding site water than in larvae or adults, irrespective of the origin of the sample. Moreover, larvae displayed a significantly different and most diversified microbial community than newly emerged adults, which appeared to be dominated by Proteobacteria. The microbiota of breeding site water significantly increased its diversity over time, suggesting the presence of a dynamic interaction among bacterial communities, breeding sites and mosquito hosts. The analysis of Wolbachia prevalence in adults from Foshan and five additional strains with different geographic origins confirmed the described pattern of dual wAlbA and wAlbB strain infection. However, differences in Wolbachia prevalence were detected, with one strain from La Reunion island showing up to 18% uninfected individuals. These findings contribute in further understanding the dynamic interaction between the ecology of larval habitats and the structure of host microbiota, including the pattern of Wolbachia infection.